The Clinical Status of Radiation Therapy in Korea in 2009 and 2013 - Kang, Jin-Kyu (Cancer Res Treat, 2016)
PURPOSE: The purpose of this study is to estimate the clinical status of radiation therapy (RT) in Korea. MATERIALS AND METHODS: We analyzed open claims data from the Health Insurance Review and Assessment Service (HIRA). The subjects were patients with malignant neoplasms who had procedure codes concerning RT in 2009 and 2013. RESULTS: The total numbers of patients who underwent RT in 2009 and 2013 were 42,483 and 56,850, respectively. The numbers of men and women were 20,012 and 22,471 in 2009 and 26,936 and 29,914 in 2013, respectively. The five most frequent RT sites were metastatic, breast, gastrointestinal, thoracic, and gynecologic cancers in 2009, and metastatic, breast, gastrointestinal, thoracic and head and neck cancers in 2013. The three leading types of cancer among men were metastatic, gastrointestinal, and thoracic, and breast, metastatic, and gynecologic among women. According to age, the most common treatment site was the central nervous system for those aged 20 years or less, the breast for those in their 30s to 50s, and metastatic sites for those in their 60s or older. CONCLUSION: Data from this study provide an overview of the clinical status of RT in Korea.